A State-wide information campaign during a pertussis epidemic in New South Wales, 2010 - Spokes, Paula J; Rosewell, Alexander E; Stephens, Alex S; McAnulty, Jeremy M (Communicable Diseases Intelligence, 2014)
Pertussis notifications increased dramatically in New South Wales in 2008, exceeding the rates in previous epidemic years. A state-wide, multi-faceted campaign was launched in March 2009 to provide information about pertussis prevention. A population-based survey was conducted using a Computer Assisted Telephone Interviewing facility to assess the effectiveness of sending letters to households with young infants. A representative sample of 1,200 adults across all 8 area health services was interviewed between July 2009 and September 2010, with responses weighted against the state population. Many respondents (39.7%) reported receiving the letter, while fewer (29.6%) reported receiving an adult pertussis booster in the last year, mostly in response to General Practitioner advice (40.4%). Letter receipt was associated with the uptake of an adult pertussis booster in the past 12 months by respondents (OR 5.8; 95%CI 4.1, 8.2) and other adults in the household (OR 5.1; 95%CI 3.5, 7.5), as well as knowledge about pertussis prevention. Health providers remain crucial for vaccination decision making; however letters may have contributed to an increased uptake of pertussis booster vaccination and knowledge. Health authorities may consider mailing households in future pertussis epidemics as a component of a wider communication strategy. Commun Dis Intell 2014;38(3):E201–E207.